PENGARUH ARUS KAS BEBAS, KEBIJAKAN DIVIDEN DAN LEVERAGETERHADAP MANAJEMEN LABA - Septiarti, Wahyu; Darmansyah, Darmansyah; Murni, Yeti (Aksara Public, 2018)
This study aims to investigate the influence of free cash flow , dividend policy and leverage to profit management in mining companies listed on the Indonesia Stock Exchange in 2010 – 2014. This study uses quantitative data that have been published in the Indonesia Stock Exchange ( BEI. The samples used in this study were 145, including 29 companies that met the study criteria , as this study using purposive sampling method in sample selection . While the method of data analysis using panel data regression techniques with Eviews 9.0 application. The result of tests performed by using chow test and Hausman test choose better fixed effect model. Results in partial test (t test) obtained that free cash flow and leverage effect on profit management while the dividend policy has no effect on profit management . While the results of simultaneous ( F test ) obtained free cash flow , dividend policy and leverage effect simultaneously to profit management . Where the error rate used is 5 % or 0.05 at significant level of 95%